The remarkable voyages of Captain Cook. - Blumberg, Rhoda frey50 (New York Bradbury Press, 1991)
An adccount of the historic adventures and achievements of the great British explorer and discoverer of Australia, Hawaii, and other Pacific Ocean lands and peoples.
Includes Biographical references and index
Keywords: Cook, James, -- 1728-1779 -- Juvenile Litrature; Voyages aro9und the world -- Juvenile Litrature; Explorers -- Great Britain -- Biography -- Juvenile Litrature; Explorers